Uji Karakteristik dan Potensi Ekstrak Bunga Telang (Clitoria Ternatea L.) di Banda Aceh menggunakan FTIR Sebagai Zat Aditif Antioksidan - Ferdius Rudia,; Saisa,; Vera Viena,; Zulhaini Sartika, (Journal Serambi Engineering, 2024)
Indonesia has biodiversity of basic ingredients that can used for making traditional medicines. Bioactive compounds also used as a source of antiinflammatory, antioxidant, anticancer, and antibacterial. Telang Flower is the One of plants that contain antioxidants. The aims of study is to determine the extract of secondary metabolic compounds contained in telang flower and secondary metabolic compounds in inhibiting the effects of free radicals. The maceration used as extraction method. The telang flower extraction result shown that contained of flavonoid compounds, alkaloids, tannins, terpenoids and steroids. The resulting bioactive compounds may act as antioxidants.